Growth Performance and Gut Development of Japanese Quails (Coturnix coturnix japonica) Fed Diets with Different Ratio of Mash and Pellet - Mehdi, Nilforoush Hamedani; Majid , Toghyani; Hossein, Irandoust (International Journal of Poultry Science, 2015)
The experiment was conducted to investigate the effect of different ratio of pellet and mash diets on performance and gut development of Japanese quails. A total of 600 quails were used in completely randomized design with 6 dietary treatments and 5 replicates of 20 quails. Dietary treatments were included of: (A) control group (100% mash); (B) 50% mash+50% pellet; (C) 75% mash+25% pellet; (D) 25% mash+75% pellet; (E) choice feeding (pellet or mash) and (F) 100% pellet. Performance parameters were determined in different growth periods. Carcass characteristics, digestive organs weight and intestinal morphology were measured at 35 day of age by slaughtering two birds per pen. Feed consumption in diet C significantly decreased and in diet D increased (p<0.05). Quails fed with diet D had the maximum daily weight gain (p<0.05). Dietary treatments had no significant effect on feed conversion ratio. The best carcass yield, greatest villus height and crypt depth in jejunum was observed in quails in diet D. Small intestine length, pancreas and proventriculus weight were not significantly affected by dietary treatments. In conclusion, feeding quails by 25% mash+75% pellet diets improved growth performance and morphometric characteristics of small intestine.